PR goals in the public sphere - Maćkowska, Renata (Univerzita Pardubice, 2006)
The ability to improve a competitive position involves the need to promote and create entrepreneurship in public organisations as well as implement modern management concepts. The strategic orientation in the management of public organisations is related to the search for identity, the vision of development and the implementation of a particular management strategy. The key issue is the incorporation of public relations into an institution’s development strategy and its close connection with the existing promotional activities. All public organisations are constantly assessed by the general public, and their functioning is seriously hindered without an appropriate level of social trust. Trust is a prerequisite for their development, necessary for implementing new ideas or operation methods. In order to win trust it is crucial to achieve probity social participation in the activities of a public organisation. The reliability and a positive image of a public organisation are necessary for the performance of its public tasks. A favourable reputation supports the link, maintaining and strengthening it, with the social environment.